Fatigue Crack Propagation Behavior of the 2195-T8 Aluminum-Lithium Alloy with a Precorroded Hole - Dejun Liu; Gan Tian; Yulong Li; Guofeng Jin; Wei Zhang (International Journal of Aerospace Engineering)
This work investigated the fatigue crack propagation behavior of the 2195-T8 Al-Li alloy with precorroded holes. The microstructure, crack growth path, and the fracture surfaces of the samples with the precorroded holes have been examined with scanning electron microscopy (SEM), electron backscatter diffraction (EBSD), and computed tomography (CT). The characteristics of the crack growth have been analyzed via fracture mechanics by employing the finite element method (FEM). The results showed that the bulk of the fatigue cracks had been initiated from the corrosion pits and corroded discontinuously and precipitated further to become intergranular. Owing to the superposed stress concentration caused by the corrosion pits, the porous region at the bottom of the precorroded hole had affected the crack propagation performance. Crack growth rates were different in multiple positions owing to the difference of KI at crack fronts.